Analytical features of microwave plasma-atomic emission spectrometry (MP-AES) for the quantitation of manganese (Mn) in wild grape (Vitis coignetiae) red wines: Comparison with inductively coupled plasma-optical emission spectrometry (ICP-OES). (15th February 2019) - Jung, Mun Yhung; Kang, Ju Hui; Choi, Yun Seo; Lee, Da Young; Lee, Ju Yeon; Park, Ji Su
Highlights: A simple and cheap MP-AES was developed and validated for the quantitation of Mn in wine. The analytical features for the MP-AES were greatly different with those of ICP-OES. Significant matrix effect in wine sample matrices was observed with MP-AES, but not with ICP-OES. The low matrix tolerance of MP-AES was overcome by a standard addition method. The contents of Mn in wild grape ( Vitis coignetiae ) wines are reported for the first time. Abstract: The analytical features of MP-AES for the determination of Mn in wine were studied as compared with ICP-OES. The optimum spectral line (403.076 nm) of MP-AES was different from that (259.373 nm) of ICP-OES. Significant matrix effect was observed with MP-AES, but not with ICP-OES. A simple and cost-effective MP-AES for the quantitation of Mn in wild grape ( Vitis coignetiae ) red wines were developed and validated. A standard addition method was used to compensate the matrix effects. The sensitivity of MP-AES was comparable to that of ICP-OES. MP-AES was sensitive, precise, accurate and reliable. The Mn concentration in the wild grape wines was in the range of 502–3627 μg L −1 . MP-AES had a distinct drawback of low matrix tolerance. However, MP-AES had a clear advantage of the low running cost due to the use of nitrogen gas generated from air with a nitrogen generator.